Analysis Of The Difficulties Of Students In Understanding Integral Material Using Visual Media - Febriyanti, Auliya; Rustam; Afri, Lisa Dwi (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
Difficulties in understanding integral material using visual media are often experienced by students, this is due to inappropriate use of visual media, and students' lack of understanding of integral material explained by the teacher. The purpose of this study was to determine the students' understanding of class XI about integral material, and the use of visual media in learning about integral material, as well as what kinds of difficulties students felt when understanding integral material. The method used in this study is a qualitative method, research data collection is done by utilizing observation data, written tests, interviews, and documentation review. The steps taken in analyzing the data are compiling the data, connecting the data, reducing, presenting the data, then making conclusions, and testing the validity of the data with crosscheck triagulation and technical triagulation. The results showed that students' understanding was still relatively low. This can be seen from the students' answers on the written test, of the 7 indicators of understanding there is only 1 indicator that is fulfilled, the indicator of restating a concept. The use of visual media is good enough, it's just that there are several stages that are not carried out, such as the stage of formulating teaching objectives by utilizing media and also teaching evaluation steps. There are 3 types of difficulties experienced by students when understanding integral material using visual media, difficulties in using concepts, difficulties in using principles, and difficulties in solving verbal problems